2021
DOI: 10.21203/rs.3.rs-416389/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Qualitative Study of Risk and Resilience in Young Adult Women With a History of Juvenile-onset Fibromyalgia

Abstract: Background. Juvenile-onset Fibromyalgia (JFM) is a chronic pain condition characterized by widespread musculoskeletal pain, fatigue, sleep difficulties, mood concerns, and other associated symptoms. Although diagnosed in childhood, JFM often persists into adulthood can result in continued physical, social, and psychological impairment. The purpose of this qualitative study was to identify themes of risk and resilience for long-term outcomes among young adults diagnosed with JFM in childhood. Methods. The sampl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…While these interpersonal processes are believed to have a profound impact on the pain sufferer’s experience of chronic pain, social isolation remains a major obstacle to recovery (Munday et al, 2021; Thomas, 2000). In one phenomenological study, for example, young adults with fibromyalgia reported isolation was a major contributor, with one participant stating, “I got to a point where I got too exhausted to really have friends” (Daffin et al, 2021, p. 8). While ultimately those who do not experience chronic pain may not truly know what it is like to be in pain, it does seem that perceived social support may have a positive impact on pain experience (Devan et al, 2018; Keefe et al, 2002; López-Martínez et al, 2008; Stevens et al, 2020; Thorn & Kuhajda, 2006).…”
Section: Outcomes and Process In Pain Management Programsmentioning
confidence: 99%
“…While these interpersonal processes are believed to have a profound impact on the pain sufferer’s experience of chronic pain, social isolation remains a major obstacle to recovery (Munday et al, 2021; Thomas, 2000). In one phenomenological study, for example, young adults with fibromyalgia reported isolation was a major contributor, with one participant stating, “I got to a point where I got too exhausted to really have friends” (Daffin et al, 2021, p. 8). While ultimately those who do not experience chronic pain may not truly know what it is like to be in pain, it does seem that perceived social support may have a positive impact on pain experience (Devan et al, 2018; Keefe et al, 2002; López-Martínez et al, 2008; Stevens et al, 2020; Thorn & Kuhajda, 2006).…”
Section: Outcomes and Process In Pain Management Programsmentioning
confidence: 99%
“…Although the proportion of qualitative research to explore protective factors of resilience has grown in recent years (Daffin et al, 2021;Rolbiecki et al, 2017;Shaw et al, 2020), the ability of resilience to enhance the long-term quality of life in patients with chronic diseases is not fully explained (Ye, 2022). There is still a knowledge gap, as few studies have focused on the maintenance of resilience in the long term (De Santis et al, 2013;Geard et al, 2018).…”
mentioning
confidence: 99%